Partial denture metal framework may harbor potentially pathogenic bacteria - Mengatto, Cristiane Machado; Marchini, Leonardo; Souza Bernardes, Luciano Angelo de; Gomes, Sabrina Carvalho; Silva, Alecsandro Moura [UNESP]; Rizzatti-Barbosa, Celia Marisa (Korean Acad Prosthodontics, 2015)
PURPOSE. The aim of this study was to characterize and compare bacterial diversity on the removable partial denture (RPD) framework over time. MATERIALS AND METHODS. This descriptive pilot study included five women who were rehabilitated with free-end mandibular RPD. The biofilm on T-bar clasps were collected 1 week (t(1)) and 4 months (t(2)) after the RPD was inserted (t(0)). Bacterial 16S rDNA was extracted and PCR amplified. Amplicons were cloned; clones were submitted to cycle sequencing, and sequences were compared with GenBank (98% similarity). RESULTS. A total of 180 sequences with more than 499 bp were obtained. Two phylogenetic trees with 84 (t(1)) and 96 (t(2)) clones represented the bacteria biofilm at the RPD. About 93% of the obtained phylotypes fell into 25 known species for t(1), and 17 for t(2), which were grouped in 5 phyla: Firmicutes (t(1)=82%; t(2)=60%), Actinobacteria (t(1)=5%; t(2)=10%), Bacteroidetes (t(1)=2%; t(2)=6%), Proteobacteria (t(1)=10%; t(2)=15%) and Fusobacteria (t(1)=1%; t(2)=8%). The libraries also include 3 novel phylotypes for t(1) and 11 for t(2). Library t(2) differs from t(1) (P=.004); t(1) is a subset of the t(2) (P=.052). Periodontal pathogens, such as F. nucleatum, were more prevalent in t(2). CONCLUSION. The biofilm composition of the RPD metal clasps changed along time after RPD wearing. The RPD framework may act as a reservoir for potentially pathogenic bacteria and the RPD wearers may benefit from regular follow-up visits and strategies on prosthesis-related oral health instructions.
Keywords: Framework; Denture plaque; Microorganisms; 16S rDNA gene; Removable partial denture